Risk Factors for Vitamin D Deficiency in Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Shi, Shanzhen; Feng, Jiaxing; Zhou, Lixiang; Li, Yu; Shi, Huaxiu (Turkish Journal of Gastroenterology, 2021)
Background: To identify risk factors for hypovitaminosis D in inflammatory bowel disease and conduct a comprehensive systematic review with meta-analysis to quantify the impact on vitamin D deficiency. Methods: We conducted a literature search of studies through PubMed, Embase, Cochrane Library, and Web of Science. In addition, relevant articles were searched manually. Studies were included if the odds ratios (OR) and 95% CI of each risk factor were reported or could be calculated. We will use the fixed-effects or random-effects model to estimate the pooled effect. Results: Out of 1018 articles, 25 eligible studies were identified, including 5826 participants. The risk factors associated with hypovitaminosis D were non-Caucasian (OR: 3.79, 95% CI: 2.68-5.34), Crohn’s disease (OR: 1.38, 95% CI: 1.21-1.56), disease activity (OR: 1.85, 95% CI: 1.61-2.13), inflammatory bowel disease-related surgery (OR: 1.61, 95% CI: 1.38-1.89), exposure to steroid (OR: 1.61, 95% CI: 1.28-2.03), and biologics (OR: 1.78, 95% CI: 1.48-2.14). In 30 ng/mL and adjusted OR subgroup, male (OR: 1.84, 95% CI: 1.47-2.31) and winter season (OR: 2.49, 95% CI: 1.69-3.67) also were risk factors, respectively. 5-aminosalicylic acid (OR: 1.10, 95% CI: 0.74-1.63) and smoking (OR: 1.19, 95% CI: 0.98-1.45) were unrelated to vitamin D deficiency. Conclusions: For vitamin D deficiency in inflammatory bowel disease, non-Caucasian, Crohn’s disease, disease activity, surgery, exposure to steroid and biologics, males are risk factors, while 5-aminosalicylic acid and smoking are not. The relationship between body mass index, winter season, exposure to immunomodulators, and vitamin D deficiency remains unclear.